Evaluación económica para la prestación del servicio de energía eléctrica al corregimiento de La Peña – Sabanalarga por medio de los lineamientos FAZNI (2019)
The interest of this investigation arises because in the Atlantic Coast there are areas that do not have electricity service or have a poor provision. This service allows communities to generate progress and improve the quality of life of the inhabitants. This research will evaluate project alternatives to define the best technical-economic option for the electric power service in the village of La Peña - Sabanalarga. This analysis takes into account the laws, norms and decrees that cover the FAZNI projects, Financial Support Fund for the Energization of Non-Interconnected Zones, which are defined by Article 82 of Law 633 of 2000; these are a special account fund of the Ministry of Mines and Energy (MME) without legal status, subject to applicable regulations and other applicable regulations (Electricaribe, 2017). The FAZNI resources come entirely from the nation and from the resources channeled by the government due to different public and private sources. As a result of the project, a comparison of scenarios was obtained through technical and economic variations to energize La Peña - Sabanalarga, ZNI, the final results show that through the creation of a Medium Voltage Network connected to the National Interconnected System (SIN) is the better solution to meet the need for electric power service.